2016
DOI: 10.5897/ajb2016.15678
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of maize landraces from Cte dIvoire

Abstract: Maize (Zea mays L.) occupies an important place among food crops in Côte d'Ivoire. However, no study on the genetic diversity of the species has been performed to date. This study aims at analyzing the diversity and genetic structure of 35 maize accessions using 10 microsatellite markers. These accessions are from different agro-ecological zones representative of the Ivorian territory. The results showed that for all accessions studied, 47 alleles were detected, with an average of 6.71 ± 2.21 alleles per locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
3
1
0
Order By: Relevance
“…This observation was consistent with the AMOVA results ( Table 2 ), which indicated that 14% of the total variation was accounted for by gene pool variations. This result is consistent with the findings of previous studies [ 42 ]. According to the F ST values, the Burkinabe gene pool was the most differentiated ( Table 3 ), in agreement with its divergence as revealed by the clustering methods (STRUCTURE, PCoA, DAPC, and NJ analyses).…”
Section: Discussionsupporting
confidence: 94%
“…This observation was consistent with the AMOVA results ( Table 2 ), which indicated that 14% of the total variation was accounted for by gene pool variations. This result is consistent with the findings of previous studies [ 42 ]. According to the F ST values, the Burkinabe gene pool was the most differentiated ( Table 3 ), in agreement with its divergence as revealed by the clustering methods (STRUCTURE, PCoA, DAPC, and NJ analyses).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the mean coefficient of genetic differentiation between accessions was identified as F = 0.16 ( Table 3 ). This result is in accordance with the result found in maize landraces from Mexico by Pineda-Hidalgo et al (2013) [ 42 ] as well as that recorded in maize landrace accessions of the Ivory Coast in 2016 [ 43 ]. Furthermore, the F index mean within the groups of populations from the three regions of South Sudan (southern region, central region, and northern region) was F = 0.37 ( Table 4 ).…”
Section: Discussionsupporting
confidence: 93%
“…Allelic patterns across these three populations show the presence of private alleles and implication for breeding is that the private alleles are an indication of new genes that could be crucial in stress tolerance. It was therefore prudent to do an analysis between the standard lines and the J lines in order to illustrate where the unique genes might be, the AMOVA observed greater variation within (90%) accessions than between (10%) them and this was similar to the findings reported by Nda et al (2016). Allelic patterns of the populations revealed that the J lines had private alleles meaning they have unique genes.…”
Section: Discussionsupporting
confidence: 74%